Photocatalytic water splitting method based on carbon nitride heterojunction superaggregation and copolymerization
By constructing nanostructures based on carbon nitride heterojunction super-aggregation method and copolymerization method, the existing photocatalyst energy level mismatch and low stability are solved, and efficient photocatalytic water decomposition under visible light is achieved, providing a A reliable non-metallic photocatalyst.
Patent Information
- Application Number
- CN202211463334.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-18
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-11-18
AI Technical Summary
Due to the mismatch of energy levels, existing photocatalytic full water dissolution reaction cannot be carried out, and the stability is not high, and the structure is easily destroyed, resulting in a decrease in photocatalytic activity.
Using carbon nitride heterojunction super-aggregation method and copolymerization method, the nanostructure is constructed, and the super-aggregation method is performed using urea and cyanuric acid, combined with 2-amino hypoxanthine modification, to generate nucleophilic donor-acceptor copolymer Conjugated polymers, used for water splitting under sunlight to produce hydrogen and oxygen.
The visible light activity and photogenerated electrons, hole separation and transmission performance of the photocatalyst are significantly improved, and high-efficiency photocatalytic water decomposition in the visible light region is achieved, providing a direct and low-cost non-metallic photocatalyst.
Smart Images

Figure CN116212914B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalysis, and in particular relates to a photocatalytic water decomposition method based on a carbon nitride heterojunction superaggregation method and a copolymerization method. Background Art
[0002] For decades, the use of fossil fuels has had significant negative environmental impacts, including carbon dioxide emissions. Therefore, the development of clean energy is imperative. Hydrogen is considered the most promising clean energy source for the 21st century. Its energy density far exceeds that of gasoline and coal, and its combustion byproduct is water, making it a promising alternative to current fossil fuels as a new industrial energy source. Currently, photocatalytic water splitting is considered an effective method for hydrogen production. However, most photocatalysts used in existing technologies are unable to fully split water due to energy level mismatches. Furthermore, most photocatalysts are unstable and easily destroyed during the photocatalytic reaction. In the active exploration of fossil fuels and the global environment, the combination of heterogeneous photocatalysts with aromatic composites has become a useful technology due to their excellent environmental friendliness and biocompatibility. The development of carbon-based photocatalysts assisted by copolymers may contribute to the advancement of hydrogen (H2) and oxygen (O2) evolution under photochemical stimulation. In contrast, the replication of charge portability severely hinders overall photocatalytic efficiency. To reduce charge recombination and improve charge mobility, insulation, and photocatalytic performance, heterostructure modification has become a popular option.
[0003] Through the above analysis, the problems and defects of the existing technology are: most of the existing photocatalysts cannot perform photocatalytic complete water splitting reaction due to energy level mismatch, and are not stable and their structures are easily destroyed, thereby reducing or even losing their photocatalytic activity. Summary of the Invention
[0004] Carbon nitride (CN), a metal-free semiconductor photocatalyst, has recently attracted the interest of researchers due to its low toxicity, enhanced sensitivity in the visible light range, and photocatalytic durability. Unfortunately, bulk CN exhibits low photocatalytic activity and is considered far from satisfactory performance. This is mainly related to the misalignment of its band gap and energy modes, which makes it a poorly visible-light-responsive photocatalyst with low surface area, quantum yield, crystallinity, and rapid recombination of photoinduced charge carriers. Several strategies have been widely adopted to improve its photocatalytic performance, including different semiconductor coupling (heterojunction), elemental dopants, and nanomaterial modification.
[0005] A photocatalytic water splitting method based on carbon nitride heterojunction superaggregation and copolymerization, comprising: constructing a potential CN-based nanostructure; establishing a superaggregation method using urea and cyanuric acid, and modifying the nanostructure using 2-aminoxanthine to generate a novel nucleophilic donor-acceptor conjugated polymer; analyzing the prepared nucleophilic donor-acceptor conjugated polymer under different characterizations, theoretical DFT and electrostatic potential maps, and applying it to water reduction and water oxidation generated by water splitting under solar light λ>420nm.
[0006] Furthermore, urea and cyanuric acid are used in a ratio of 2:1 to prepare a conjugated polymer.
[0007] Furthermore, the preparation method of the nucleophilic donor-acceptor conjugated polymer comprises the following steps:
[0008] Step 1: Grind urea and cyanuric acid thoroughly in a mortar to obtain a fine powder; dissolve the obtained fine powder in distilled water and stir continuously until all the water evaporates to produce a solid residue;
[0009] Step 2: The obtained solid product is transferred to a crucible and calcined; the calcined product is completely ground into fine slag, washed with ethanol and double distilled water, and dried to obtain CNC;
[0010] Step 3: Using urea, cyanuric acid, and different concentrations of organic conjugated monomers to analyze CNC catalysts, CNC-G10.0, and CNC-G15.0 synthetic samples, the supramolecular pre-organization and copolymerization process were realized;
[0011] Step 4: A separate copolymerization process is carried out between urea and guanine monomer to obtain CN-G10.0; without inducing cyanuric acid and guanine monomer, 10g of urea is taken to synthesize the original CN.
[0012] Furthermore, in step 1, 10 g of urea and 5 g of cyanuric acid were weighed and ground in a mortar to obtain a fine powder.
[0013] Furthermore, in step 1, the fine powder was dissolved in 60 mL of distilled water and stirred continuously at 90 °C.
[0014] Furthermore, in step 2, the solid product was calcined at 550°C for 4 h at a heating rate of 2.3 C min-1.
[0015] Furthermore, in step 2, the calcined product is washed and then transferred to 80° C. for drying.
[0016] Furthermore, in step three, 10 g of urea, 5 g of cyanuric acid and an organic conjugated monomer are weighed for supramolecular pre-organization and copolymerization; wherein the organic conjugated monomer is 2-aminohypoxanthine.
[0017] Furthermore, in step 3, 10.0 and 15.0 mg are the amounts of guanine monomers introduced into the mixture.
[0018] Furthermore, in step 4, 10 g of urea and 10.0 mg of guanine monomer were weighed and subjected to separate copolymerization processes.
[0019] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:
[0020] First, the present invention provides a simple and effective copolymerization method and a supramolecular pre-organization method for the first time, proposing a potential CN-based nanostructure. First, the present invention uses urea and melamine to establish a superaggregation method, and then modifies this nanostructure with 2-aminoxanthine (guanine) to generate a new type of nucleophilic donor-acceptor (DA) conjugated polymer. The samples prepared by the present invention are easier to analyze under different characterizations, theoretical DFT and electrostatic potential maps, and are successfully used to decompose water under sunlight (λ>420nm) to produce hydrogen and oxygen. The heterojunction prepared by the present invention exhibits significant visible light activity and excellent separation and transport properties of photogenerated electrons and holes, which explains its high activity in the process of splitting water into hydrogen (H2) and oxygen (O2). More notably, this heterostructure has been reported for the first time for photocatalytic water decomposition in the visible light region. Therefore, the present invention provides a direct and low-cost method to develop and construct a very reliable non-metallic photocatalyst.
[0021] Initially, this study demonstrated a hyperpolymerization method (CNC) of urea and cyanuric acid, and modified these composites (CN-G and CNC-G) with 2-aminohypoxanthine (guanine) to achieve a novel intramolecular donor-acceptor (DA) conjugated polymer. The synthesized samples, particularly the nitrogen-rich CN-G and CNC-G, possessed a pyrimidine-imidazole ring system with a coupled double bond, exhibiting superior donor-acceptor (DA) properties and potentially greater stability. Basic characterization and theoretical DFT calculations successfully characterized and explained the optimized properties of the improved samples as derived from their broadened light absorption range and their electronic integrity, quenched in their highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO), respectively. Furthermore, the resulting photocatalysts, particularly the optimized CNC-G10.0, were found to be the most efficient photocatalytic materials for H₂ production from water splitting under visible light (λ ≥ 420 nm).
[0022] Second, regarding the technical solution as a whole or from the perspective of the product, the technical effects and advantages of the technical solution to be protected by the present invention are described in detail as follows:
[0023] The present invention proposes for the first time a simple and efficient supramolecular pre-organized copolymerization method to synthesize potential carbon nitride (CN)-based composite materials.
[0024] The development of copolymer-assisted carbon-based photocatalysts can well promote the development of photocatalytically excited hydrogen (H2) and oxygen (O2) evolution.
[0025] Heterostructure modification has emerged as an attractive option to reduce photogenerated charge recombination while improving charge mobility, isolation, and photocatalytic efficiency.
[0026] Third, the present invention's technical solution fills a technological gap in the industry, both domestically and internationally. The design of supramolecular pre-organization methods has attracted significant interest as an effective self-templating approach to appropriately adjust the nanostructure of CNs to enhance their overall photocatalytic activity. Furthermore, it is noteworthy that supramolecular reactions of urea-based CNs with cyanuric acid (CNC) mostly exhibit extremely stable structures, with urea molecules readily forming bonds via hydrogen bonds (NH…N and NH…O). However, the off-centered configuration of CNCs results in permeable CNs with high surface areas. In contrast, molecular doping (copolymerization) is a cost-effective approach to significantly tune the local electronic structure of CNs, aiming to enhance visible light absorption and promote interfacial charge carrier separation, thereby improving the overall photocatalytic activity of simple CNs. Here, a facile and effective supramolecular pre-organization and copolymerization method is proposed for the first time to synthesize potential CN-based composites. Initially, a method for superaggregation of urea and cyanuric acid was demonstrated, and after modifying these composites with 2-aminohypoxanthine (guanine), unique intramolecular donor-acceptor (DA) conjugated materials were achieved. Advances in copolymer-assisted carbon-based photocatalysts can well promote the release of hydrogen (H2) and oxygen (O2) upon photocatalytic excitation. Furthermore, charge transportability replication is a major obstacle to overall photocatalytic efficiency. In this context, heterostructure modification has become an attractive option to reduce charge recombination while improving charge mobility, isolation, and photocatalytic efficiency. The constructed heterojunction exhibits remarkable visible light performance, as well as excellent isolation and transition properties of electron carriers and holes, which are crucial for its high activity throughout the water splitting process to produce hydrogen (H2) and oxygen (O2). In turn, the resulting material improves photocatalytic performance by providing considerable surface active sites, increasing its adsorption capacity and reducing the aggregated band structure of CN, thereby enabling its high performance under visible light illumination. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0028] Figure 1 This is a flow chart of a method for preparing a nucleophilic donor-acceptor conjugated polymer provided by an embodiment of the present invention;
[0029] Figure 2 (a) is an X-ray diffraction (XRD) pattern provided by an embodiment of the present invention; (b) is a schematic diagram of the Fourier transform infrared spectroscopy (FTIR) of all synthesized materials; (c) is a schematic diagram of the N2 adsorption-desorption isotherm (77K); (d) is a pore size distribution diagram of the original CN and the advanced CNC-G10.0 sample; (e) is a photoluminescence spectrum (PL) diagram; (f) is a UV-visible DRS spectrum diagram of all synthesized materials; (g) is a schematic diagram of the C / N molar ratio of all materials; (h) is an elemental analysis spectrum (EAS) diagram of the original CN; (i) is a schematic diagram of the EPR spectrum of the original CN and the advanced CNC-G10.0 sample under visible light irradiation (λ = 420nm);
[0030] Figure 3 (a) is a scanning electron microscope image of CN provided by an embodiment of the present invention; (b) is a scanning electron microscope image of CNC; (c) is a scanning electron microscope image of CNC-G (S0.0); (d) is a transmission electron microscope (TEM) image of CN; (e) is a scanning electron microscope image of CNC; (f) is a scanning electron microscope image of CNC-G10.0; and (g-i) are electron dispersion x-ray analysis (EDX) images of the high-quality sample CNC-G10.0;
[0031] Figure 4 (a) and (b) are schematic diagrams of XPS results of the measurement spectra provided in the embodiments of the present invention; (c) and (d) are c1 of CN and CNC-G10.0, (e) and (f) N1, and (g), (h) and (j) are high-resolution sulfur spectra of CNC-G10.0 material;
[0032] Figure 5 (a) is a schematic diagram of the optimized geometric structure provided by an embodiment of the present invention; (b) is the HOMO, (c) the LUMO of CN; (d) is a schematic diagram of the optimized geometric structure; (e) is the HOMO, (f) is the LUMO of CN-g10.0; (g) is the adsorption of guanine on CN, and (h) is a schematic diagram of the DOS of CN;
[0033] Figure 6Schematic diagram of the overall photocatalytic water splitting provided by an embodiment of the present invention; wherein, Figure (a) is a schematic diagram of the HER time function rate b / w CN, CNC, CN-G10.0 & CNC-G10.0; (b) is a schematic diagram of the stability test of CN-G10.0 and CNC-G10.0; (c) is a diagram of the yield of all synthetic samples; (d) is a schematic diagram of the photocatalytic reaction at the incident light wavelength; (e) is a diagram of the conduction band performance; (f) is a schematic diagram of the OER time function rate b / w CN, CNC, CN-G10.0 and CNC-G10.0; (g) is a diagram of the stability test of CN-G10.0 and CNC-G10.0; (h) is a diagram of the OER yield of all synthetic samples; (i) is a diagram of the valence band OER performance under visible light illumination;
[0034] Figure 7 This is a schematic diagram of the photocatalytic principle of CNC-G10.0 under visible light illumination provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0036] In response to the problems existing in the prior art, the present invention provides a photocatalytic water splitting method based on carbon nitride heterojunction superaggregation method and copolymerization method. The present invention is described in detail below with reference to the accompanying drawings.
[0037] In response to the problems of the prior art, the present invention provides an alternative to heterostructure modification in order to reduce charge recombination and improve charge mobility, isolation, and photocatalytic effects. Here, for the first time, a simple and effective copolymerization and supramolecular pre-organization method are combined to create a forward-looking CN-based nanostructure. More notably, the increased consistency of this heterostructure is reported for the first time for photocatalytic water splitting in the visible light region. Therefore, the present invention provides a direct and low-cost method for the development and construction of very reliable metal-free photocatalysts.
[0038] Advances in copolymer-assisted carbon-based photocatalysts can significantly enhance the release of photocatalytically excited hydrogen (H2) and oxygen (O2). Furthermore, the replication of charge transportability is a major obstacle to overall photocatalytic efficiency. In this context, heterostructural modification has emerged as an attractive option to reduce charge recombination while improving charge mobility, isolation, and photocatalytic efficiency. Here, a facile and efficient supramolecular preorganization and copolymerization method is proposed for the first time to synthesize potential carbon nitride (CN)-based composites. Initially, a superaggregation approach was demonstrated for urea and cyanuric acid (CNC), and these composites (CN-G and CNC-G) were modified with 2-aminohypoxanthine (guanine) to achieve novel intramolecular donor-acceptor (DA) conjugated polymers. The as-synthesized samples, particularly CN-G and CNC-G, enriched by nitrogen content and thus bearing pyrimidine-imidazole ring systems with conjugated double bonds, were highlighted as superior donor-acceptor (DA) and potentially more stable. Several spindle characterizations and theoretical DFT calculations successfully characterized the multifunctional structural optimization of the modified samples and accelerated the optical absorption range and the electronic integrity of their quenching in the redundant molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO), respectively. Furthermore, the resulting photocatalyst, particularly the superior CNC-G10.0, was identified as a highly promising material for photocatalytic activity in water splitting to produce H2 and O2 under visible light (λ = 420 nm) with controlled selectivity. The current research work demonstrates unique, low-cost, abundant, and time-consuming characteristics, thus providing a foothold for a new and revitalized concept in photocatalytic diversity.
[0039] In order to enable those skilled in the art to fully understand how to implement the present invention, this section provides an explanatory embodiment that expands on the technical solutions of the claims.
[0040] The photocatalytic water splitting method based on carbon nitride heterojunction superaggregation and copolymerization provided in an embodiment of the present invention includes: constructing a potential CN-based nanostructure; establishing a superaggregation method using urea and cyanuric acid, and modifying the nanostructure using 2-aminoxanthine to generate a novel nucleophilic donor-acceptor conjugated polymer; analyzing the prepared nucleophilic donor-acceptor conjugated polymer under different characterizations, theoretical DFT and electrostatic potential maps, and applying it to water reduction and water oxidation generated by water splitting under solar light λ>420nm.
[0041] In the embodiment of the present invention, urea and cyanuric acid are used in a ratio of 2:1 to prepare a conjugated polymer.
[0042] like Figure 1 As shown, the preparation method of the nucleophilic donor-acceptor conjugated polymer provided in an embodiment of the present invention comprises the following steps:
[0043] S101, completely grinding urea and cyanuric acid in a mortar to obtain a fine powder; dissolving the obtained fine powder in distilled water with continuous stirring until all the water evaporates to produce a solid residue;
[0044] S102, transferring the obtained solid product to a crucible and calcining the product; grinding the calcined product into fine slag, washing it with ethanol and double-distilled water, and drying it to obtain CNC;
[0045] S103, using urea, cyanuric acid and different concentrations of organic conjugated monomers to analyze CNC catalysts, CNC-G10.0 and CNC-G15.0 synthesis samples to achieve supramolecular pre-organization and copolymerization processes;
[0046] S104, a separate copolymerization process is carried out between urea and guanine monomer to obtain CN-G10.0; without inducing cyanuric acid and guanine monomer, 10g of urea is taken to synthesize the original CN.
[0047] In step S101 provided in an embodiment of the present invention, 10 g of urea and 5 g of cyanuric acid were weighed and ground in a mortar to obtain fine powder; the fine powder was dissolved in 60 mL of distilled water and continuously stirred at 90°C.
[0048] In step S102 provided in an embodiment of the present invention, the solid product is calcined at 550° C. for 4 h at a heating rate of 2.3 cm −1 ; the calcined product is washed and then transferred to 80° C. for drying.
[0049] In step S103 provided by an embodiment of the present invention, 10 g of urea, 5 g of cyanuric acid and an organic conjugated monomer are weighed for supramolecular pre-organization and copolymerization; wherein the organic conjugated monomer is 2-aminohypoxanthine.
[0050] In step S103 provided in an embodiment of the present invention, 10.0 and 15.0 mg are the amounts of guanine monomers added to the mixture; in S104, 10 g of urea and 10.0 mg of guanine monomers are weighed and subjected to separate copolymerization processes.
[0051] In order to prove the creativity and technical value of the technical solution of the present invention, this section provides application examples of the claimed technical solution on specific products or related technologies.
[0052] The technical solution of the synthetic material provided by the embodiment of the present invention is as follows: 10g of urea and 5g of cyanuric acid (2:1) are selected for material preparation. First, urea and cyanuric acid are completely ground in a mortar to obtain a fine powder. Then, the obtained fine powder is dissolved in 60mL of distilled water and stirred continuously at 90°C until all the water evaporates to produce a solid residue. Then, the obtained solid product is transferred to a crucible and then heated at 550°C at a heating rate of (2.3C min -1) was calcined for 4 hours. The calcined product was completely ground into a fine residue, then washed with ethanol and double distilled water, transferred to 80°C for drying, and named CNC. Similarly, the supramolecular pre-organization and copolymerization process was carried out by 10 grams of urea, 5 grams of cyanuric acid, and different concentrations of organic conjugated monomers such as 2-aminohypoxanthine (guanine) using the same method to explore CNC catalysts and CNC-G10.0 and CNC-G15.0 synthesis samples (10.0 and 15.0 mg are the amounts of guanine monomers entering the mixture). A separate copolymerization process (molecular engineering) with the same steps as above was carried out between urea (10 g) and guanine monomer (10.0 mg), named CN-G10.0. Under the above steps, 10 g of urea was taken to synthesize the original CN without inducing cyanuric acid and guanine monomer, and named CN respectively.
[0053] Figure 2 (a) X-ray diffraction (XRD); (b) Fourier transform infrared spectroscopy (FTIR) of all synthesized materials; (c) N2 adsorption-desorption isotherm (77K); (d) pore size distribution diagram of original CN and advanced CNC-G10.0 sample; (e) photoluminescence spectrum (PL); (f) UV-visible DRS spectrum of all synthesized materials; (g) C / N molar ratio of all materials; (h) elemental analysis spectrum (EAS) of original CN; (i) EPR spectrum of original CN and advanced CNC-G10.0 sample under visible light irradiation (λ=420nm).
[0054] Figure 3 (a) is CN, (b) is CNC, and (c) is CNC-G scanning electron microscopy (S0.0); (d) is the transmission electron microscopy (TEM) image of CN; (e) is CNC, (f) is CNC-G10.0, and (g~i) electron dispersive X-ray analysis (EDX) of the high-quality sample CNC-G10.0.
[0055] Figure 4 (a) and (b) are the XPS results of the measured spectra; (c) and (d) are c1 of CN and CNC-G10.0, (e) and (f) N1, (g), (h) and (j) are the high-resolution sulfur spectra of CNC-G10.0 material.
[0056] Figure 5 (a) is the optimized geometric structure; (b) is the HOMO, (c) is the LUMO of CN; (d) is the optimized geometric structure; (e) is the HOMO, (f) is the LUMO of CN-g10.0; (g) is the adsorption of guanine on CN, and (h) is the DOS of CN.
[0057] Figure 6Schematic diagram of the overall photocatalytic water splitting; Figure 6 (a) HER time function rate b / w CN, CNC, CN-G10.0 & CNC-G10.0; (b) stability test CN-G10.0 and CNC-G10.0; (c) yield of all synthesized samples; (d) photocatalytic reaction of incident light wavelength; (e) conduction band performance; (f) OER time function rate b / w CN, CNC, CN-G10.0 and CNC-G10.0; (g) stability test CN-G10.0 and CNC-G10.0; (h) OER yield of all synthesized samples; (i) valence band OER performance under visible light illumination.
[0058] The embodiment of the present invention adopts the photocatalytic overall water splitting mechanism of CNC-G10.0 hybrid reaction as follows Figure 7 As shown. The photocatalytic yield of H2 and O2 depends largely on the surface area, band gap, charge transport dissociation efficiency and electron density band of the semiconductor. In this heterostructure scheme, CNC and guanine copolymers are expected to combine and provide significant simultaneous synergy. Both (CNC and guanine) can be stimulated by visible irradiation at the same time, thereby improving performance. In addition, they can also prevent mutual deterioration, making the catalytic process more stable and efficient. In addition, the formation of an energy transfer network through heterostructure synthesis may greatly accelerate the electron distribution path, which is consistent with the technical solutions published earlier. In particular, the present invention found that the microstructure of the CNC-G10.0 hybrid is built on a special type-II heterostructure, in which the excited electrons of the material intersect and are fully aligned.
[0059] Due to its favorable environmental and biocompatibility, the development of carbon-based photocatalysts with the assistance of copolymers may contribute to the photochemical stimulation of hydrogen (H2) and oxygen (O2). In contrast, the charge portability duplication seriously hinders the overall photocatalytic efficiency.
[0060] During the photocatalytic water splitting process, visible light irradiation usually leads to the generation of electron-hole pairs in the (CNC-G10.0) sample. The electron flow from guanine to CN increases the binding energy of CN. Subsequently, the photoexcited electrons move from the CB of CN to the CB of the copolymerized CNC, while the holes migrate from the VB of CN to the VB of the copolymerized CNC. Therefore, the photoexcited electrons are stored in the CB of the copolymerized CNC, while the holes occupy the VB of CN, which is conducive to the separation of the photoexcited particles. At the edge of the copolymerized CNC, the electrons eventually bind to the H +The combination produces H2. Simultaneously, the pores of CNC-G undergo water oxidation to form O2. Grabowski and Rotkiewicz noted that in the intramolecular donor-acceptor conjugated composite, the aromatic ring acts as an electron acceptor, while the nitrogen unit containing a lone pair of electrons acts as an electron donor, leading to the stimulation of charge transfer. Analysis previously conducted by the present invention showed that the ratio of photoexcited electrons on the acceptor in CNC-G is comparable to the number of electrons on th. The present invention widely believes that the exciton particles in the donor are also allocated to the acceptor interaction, and compared with the photoinduced electrons of the integrated HOMO-LUMO progression in CN, they have a longer lifetime and a lower probability of conjugation with the hole, which is believed to be more conducive to charge separation.
[0061] The development of copolymer-assisted carbon-based photocatalysts can well promote the development of photocatalytically stimulated hydrogen (H2) and oxygen (O2) evolution. In addition, charge portability replication is a huge obstacle to overall photocatalytic efficiency. In this context, heterostructural modification has emerged as an attractive option to reduce charge recombination while improving charge mobility, isolation and photocatalytic efficiency. This paper presents for the first time a facile and efficient supramolecular pre-organization and copolymerization method to synthesize potential carbon nitride (CN)-based composites.
[0062] Initially, this study demonstrated the analytically demonstrated hyperpolymerization of urea and cyanuric acid (CNC). These composites (CN-G and CNC-G) were modified with 2-aminohypoxanthine (guanine) to achieve a novel intramolecular donor-acceptor (DA) conjugated polymer. The synthesized samples, particularly the nitrogen-rich CN-G and CNC-G, possessed a double-bonded pyrimidine-imidazole ring system, exhibiting superior donor-acceptor (DA) properties and potentially improved stability. Several spindle characterizations and theoretical DFT calculations successfully characterized the improved samples' multifunctional structural optimization, accelerating their optical absorption range and electronic integrity, as quenched in their redundant molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO), respectively. Furthermore, the resulting photocatalysts, particularly the superior CNC-G10.0, were shown to exhibit high potential for H₂ water splitting and photocatalytic activity under visible light (λ = 420 nm), with excellent selectivity. While the current analytical work is unique and cost-effective, it remains time-consuming, offering a new perspective on photocatalytic diversity.
[0063] The embodiments of the present invention have achieved some positive effects during the development or use process and indeed have great advantages over the existing technology. The following content describes them in conjunction with data, charts, etc. of the experimental process.
[0064] like Figure 2 As shown in Figure 5, CN and their composite catalysts were demonstrated using X-ray powder diffraction (XRD) patterns to resolve their crystal structures. Figure 2As shown in a, all samples are characterized by two main peaks, located at 13.1° at (1 0 0) and 27.8° at (0 0 2) crystal indices. Therefore, the main peak at 27.8° (0 0 2) is a large-amplitude broad peak that evaluates the interlayer stacking of graphite segments and is powered by their interruption. It is worth noting that the interlayer distance between these segments is recorded as 0.326nm for all samples. Similarly, the peak assigned to 13.1° (1 0 0) has a small intensity peak and exhibits an in-plane analogue of the tri-s-triazine unit and suggests that the interlayer distance between these stacks is 0.676nm. At the same time, the Fourier transform infrared spectroscopy (FTIR) of the samples was analyzed to erode their functional absorption phenomena, such as Figure 2 As shown in b. All samples reflect similar peaks, so there is no change in their crystal structure (XRD) and core chemical skeleton (FTIR) during the supramolecular pre-organization and copolymerization method with CN. In short, the peak band in the range of 1100-1800 cm-1 indicates the bending / stretching vibration of the aromatic CN heterocyclic repeating unit. Closely, a similar peak band quenched from 2900 to 3300 cm-1 is elevated due to the adsorption of water molecules and NH vibration. Similarly, the peak band optimized at the 800 cm-1 position releases the breathing characteristics of the s-triazine (CN) unit. In addition, the peak band is located at 3100–3400 cm-1, thus indicating a decrease in the content of uncondensed amine (-NH2) groups. Finally, the Brunauer Emmett Teller (BET) analysis (N2 adsorption-desorption isotherm) of the original CN and its modified samples was demonstrated to extract their specific surface area, porosity and its adsorption phenomena, such as Figure 2 c. According to the classification implemented by the IUPAC system, all our samples have an H3 type after the IV hysteresis loop, thus proving the presence of mesoporous lamellar features in the samples. Inspired by this, the specific surface area of the parent CN was evaluated to be 39.42 m2 / g, so this surface area increased significantly after the integration of cyanuric acid (supramolecular pre-organization) into the CN matrix (CNC = 107.57 m2 / g). At the same time, the combination of organic monomers with CNC and original CN significantly increased the surface area after the copolymerization process (CN-G10.0 = 123.19 m2 / g, CNC-G10.0 = 179.26 m2 / g), which is the high photocatalytic performance under solar illumination. In fact, under visible light, the high surface area of the material provides sufficient space for the photocatalytic reaction by generating active sites, which facilitates photogenerated electrons and holes and regards them as superior candidates for the heterogeneous catalysis of overall water splitting. In comparison, the pore size distribution curves of CN and modified materials are shown in Figure 4. Figure 2d. The results show that the combination of cyanuric acid and monomeric guanine leads to considerable changes in the chemical structure and electronic properties of CN, as well as significant changes in its surface. The photoluminescence (PL) spectra of the samples were studied to exclude the transfer, emission and recombination of photoexcited electrons and holes and their probes under visible light, such as Figure 2 As shown in e. The results show a broadband PL emission spectrum of the original CN sample, thus indicating that the photogenerated electrons and holes accelerate the process of photocatalytic reaction under the absorption phenomenon. Similarly, after the integration of cyanuric acid as well as guanine monomers in CN, this width of the PL intensity of the band signal decreases, which indicates that the charge recombination of the photogenerated electrons is weakened, which is closely related to these two processes under sunlight. This modification inhibits the transport of photogenerated electrons and also affects their specific surface area, pore volume, the lifetime of their absorption and reduces their PL intensity. Similarly, the superior sample, namely CNC-G10.0, is attributed to the longer wavelength PL emission spectrum compared to the other samples, which indulges in lowering its calculated band gap from UV-Vis DRS analysis. As Figure 2 As shown in f, UV-visible diffuse reflectance spectroscopy (DRS) of the samples confirmed their photoelectric absorptivity and band structure. In the same way, pure CN showed consistent permeability at 410 nm and refuted the moderate band structure of 3.02 eV. In contrast, the customized materials (CNC, CN-G10.0, CNC-G15.0 and CNC-G10.0) optimized the extrapolated threshold absorptivity, and the ideal sample (CNC-G10.0) was found to have an absorption edge of 510 nm and a possible band gap of 2.3 eV. Similarly, after the modification process, the consistency of the red shift was effectively accelerated to a deeper region due to the exclusion of carbon and nitrogen. Due to their association with the subsequent vacancy-related semiconductor C3+ states, the necessary amount of carbon and nitrogen released excess photogenerated electrons and holes, thereby reducing the estimated band gap.
[0065] like Figure 7 As shown, the overall photocatalytic water splitting mechanism using CNC-G10.0 mixture is as follows Figure 6As shown, the photocatalytic yields of H₂ and O₂ are largely dependent on the surface area, band gap, charge transfer dissociation efficiency, and electron density band of the semiconductor. Within the overall heterostructure scenario, the combination of CNC and guanine copolymers is expected to provide significant simultaneous synergy. Both (CNC and guanine) can be stimulated simultaneously by visible radiation, thereby enhancing performance. Furthermore, they prevent each other from degrading, resulting in a more stable and efficient catalytic process. Furthermore, the energy transfer network formed through heterostructure synthesis may significantly accelerate the electron distribution path, consistent with previously published research. In particular, the microstructure of the CNC-G10.0 hybrid was found to be based on a specific type-II heterostructure, in which the excited electrons of the materials intersect and perfectly align. During photocatalytic water splitting, visible light irradiation typically leads to the generation of electron-hole pairs within the (CNC-G10.0) sample. This electron flow from guanine to CN increases the binding energy of CN. Subsequently, photoexcited electrons migrate from the CN's CB to the CNC's CB, while holes migrate from the CN's VB to the CNC's VB. Therefore, the photoexcited electrons are stored in the CB of the copolymerized CNC, while the holes occupy the VB of the CN, which is conducive to the separation of the photoexcited particles. At the boundaries of the copolymerized CNC, the electrons eventually combine with H+ to generate H2. At the same time, the holes of CNC-G undergo an oxidation process with water to form O2. Grabowski and Rotkiewicz pointed out that in the intramolecular donor-acceptor conjugated composite, the aromatic ring acts as an electron acceptor, while the nitrogen unit containing a lone pair of electrons acts as an electron donor, resulting in the stimulation of charge transfer. Studies have shown that the proportion of photoexcited electrons on the acceptor in CNC-G is comparable to the number of electrons on the LUMO region in CN. It is also generally believed that compared with the photogenerated electrons from the integrated HOMO-LUMO series in CN, the exciton particles in the donor (also assigned to the acceptor interaction) have a longer lifetime and less probability of conjugation with holes, which is considered to be more conducive to an effective charge separation effect.
[0066] The above description is only a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with this technical field within the technical scope disclosed by the present invention and within the spirit and principles of the present invention should be covered by the scope of protection of the present invention.
Claims
1. A photocatalytic water splitting method based on carbon nitride heterojunction super aggregation method and copolymerization method, characterized in that: include: To construct potential CN-based nanostructures, a superaggregation method was established using urea and cyanuric acid, and the nanostructures were modified with guanine to generate novel nucleophilic donor-acceptor conjugated polymers; The preparation method of the nucleophilic donor-acceptor conjugated polymer comprises: weighing 10g of urea, 5g of cyanuric acid and an organic conjugated monomer for supramolecular pre-organization and copolymerization; wherein the organic conjugated monomer is guanine.
2. The photocatalytic water splitting method based on carbon nitride heterojunction super aggregation method and copolymerization method as claimed in claim 1, characterized in that: 10.0 g or 15.0 mg is the amount of guanine monomer that goes into the mixture.
